2013
DOI: 10.1007/s12282-013-0478-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of phosphorylated HER2 in HER2-positive breast cancer patients treated with adjuvant trastuzumab

Abstract: This retrospective cohort study suggests that a lower expression level of HER2 and high expression levels of pHER2 and p53 may indicate a worse prognosis in HER2-positive breast cancer patients treated with trastuzumab and chemotherapy. Further studies are needed to evaluate pHER2 expression in HER2-positive breast cancer as a prognostic and/or predictive marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
3
8
0
1
Order By: Relevance
“…von Minckwitz et al (9) and Gwak et al (10) reported four molecular outcomes in detail following surgery. Patients with HER2-amplified or hormone receptor-negative may have an additional benefit from neoadjuvant therapy to achieve pCR, which suggests that patients with different HER2 or hormone receptor status have different sensitivity for neoadjuvant therapy, although there were poor prognostic factors (22). The similar association between molecularly and pCR has been reported previously.…”
Section: Heterogeneity Effect Size ----------------------------------supporting
confidence: 71%
“…von Minckwitz et al (9) and Gwak et al (10) reported four molecular outcomes in detail following surgery. Patients with HER2-amplified or hormone receptor-negative may have an additional benefit from neoadjuvant therapy to achieve pCR, which suggests that patients with different HER2 or hormone receptor status have different sensitivity for neoadjuvant therapy, although there were poor prognostic factors (22). The similar association between molecularly and pCR has been reported previously.…”
Section: Heterogeneity Effect Size ----------------------------------supporting
confidence: 71%
“…Bauer ve arkadaşları (14) çalışmasında triple negatif grupta ortanca tümör çapını 22 mm, Japonya'daki çalışmada ise Her2 pozitif grupta ortanca tümör çapı 21 mm saptanmıştır (13). Çalışmamızda da iki gruptaki hastaların ortanca tümör çapı 25 mm civarında bulunmuştur.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Trastuzumab, used as the first‐line treatment for HER2‐positive metastatic breast cancer, is a fully humanized version of a murine HER2‐targeted IgG1 monoclonal antibody with a molecular mass of 148 400 Da . Since it was first approved by FDA in 1998, trastuzumab has achieved great clinical success and saved thousands of lives of breast cancer patients.…”
Section: Targeted Biopharmaceuticals For Breast Cancer Treatmentmentioning
confidence: 99%